(untitled) (Innovative technologies, 2026)
An accident (a breach) in a dam or reservoir dyke causes a large mass of water to be compressed and displaced through the breach, dramatically increasing the flow velocity and its dynamic impact on the dam bottom and reservoir basin. This results in the breach widening and significant deformation of the reservoir basin’s relief, which takes on a complex topological shape. After emergency situations have been resolved, damaged (breached) sections of the dam have been repaired, and reservoir operations have been restored, scientific and technical issues related to determining the reservoir’s water volume and accurately recording it arise. This article presents a solution to the problem of determining the elevation marks of a reservoir bottom with complex topography, using a specific facility as an example.